Superiorization of incremental optimization algorithms for statistical tomographic image reconstruction. (1st March 2017) - Helou, E S; Zibetti, M V W; Miqueles, E X
Abstract: We propose the superiorization of incremental algorithms for tomographic image reconstruction. The resulting methods follow a better path in its way to finding the optimal solution for the maximum likelihood problem in the sense that they are closer to the Pareto optimal curve than the non-superiorized techniques. A new scaled gradient iteration is proposed and three superiorization schemes are evaluated. Theoretical analysis of the methods as well as computational experiments with both synthetic and real data are provided.